(untitled) (Revista de Investigaciones Universidad del Quindío, 2021)
Understanding why the customer acquires a product or service has a new role in the context of the COVID-19 pandemic. The Job to be Done methodology proposes to detect the reason why the consumer hires a product or service, and from here emanates the possibility of generating an effective solution for the client. This project seeks to detect the work that the person who orders take-out food wants to do in the family business "Super Tortas SagundoMR" located in Tenosique, Tabasco; and in this way build strategies focused on said JTBD. For this, qualitative and quantitative research was carried out with a cross-sectional scope, through interviews and observation, as well as the use of the Job Prioritization methodology (Silverstein and De Carlo, 2012). It was found that this company has potential validated by its consumers in home delivery and that their reasons for hiring this service are based on the taste of the product. There is potential to re-establish home service using the push that brand equity has represented over the past 30 years and the validation of the winning JTBD.